Factors protecting against a decline in physical activity during the COVID-19 pandemic - Fearnbach, S. N.; Flanagan, E. W.; Höchsmann, C.; Beyl, R. A.; Altazan, A. D.; Martin, C. K.; Redman, L. M. (Medicine & Science in Sports & Exercise, 2021)
Purpose: The spread of COVID-19 and the associated stay-at-home orders and shutdowns of gyms and fitness centers have drastically influenced health behaviors leading to widespread reductions in physical activity (PA). The recent Call to Action from the American College of Sports Medicine has promoted "innovative strategies to promote PA during the COVID-19 pandemic." We aimed to identify individual-level factors that protected against declines in PA levels amid the COVID-19 restrictions. Methods: We used the Pennington Biomedical COVID-19 Health Behaviors Survey for our analyses and used mixed-effect linear and generalized linear models to estimate the effects of individual-level factors on changes in PA levels during the COVID-19 restrictions. Results: Participants (n = 4376) provided information on PA behaviors before and during the COVID-19 shutdown. Overall, PA levels declined by a mean ± SD of 112 ± 1460 MET·min·wk-1 during the COVID-19 shutdown; however, changes in PA were heterogeneous, with 55% of the participants reporting increases in or maintenance of PA during that time. Several social and demographic factors were significantly related to declines in PA, including high prepandemic PA levels, living alone (difference = 118 MET·min·wk-1), low household income (difference between the highest and the lowest income group = 363 MET·min·wk-1), COVID-19-related changes in income (difference = 110 MET·min·wk-1), and loss of employment (difference = 168 MET·min·wk-1). The substitution of prepandemic gym attendance with the purchase and use of home exercise equipment or exercise through virtual fitness platforms promoted increases in PA during the COVID-19 shutdown. Conclusions: While promoting PA through the COVID-19 pandemic, it is important to consider demographic factors, which greatly influence health behaviors and implementation of, and access to, replacement behaviors. The promotion of such strategies could help maintain PA levels during potential future stay-at-home orders.